PENGARUH KARAKTERISTIK SISTEM INFORMASI AKUNTANSI MANAJEMEN TERHADAP KINERJA ORGANISASI DENGAN TINGKAT DESENTRALISASI SEBAGAI VARIABEL MODERATING - Edisah Putra Nainggolan (Jurnal Riset AKuntansi dan Bisnis, 2015)
Management accounting information systems (SIAM) aims to provide theinformation needed to facilitate monitoring and assessment of the organization'sactions. There are four characteristics of management accounting informationsystems (SIAM), that is broad scope, aggregation, integration, timeliness. This studyexamined the effect of the characteristic management accounting information systemwith the organization performance to the level of decentralization as a moderatingvariable. The expected is to support the implementation of SIAM to improvingorganizational performance. This study formed research survey that usequestionnaire instrument to collect the necessary data. Questionnaire distributed tothe head of unit / branch manager at Tirtanadi Provinsi North Sumatera. Quality ofthe data generated from the use of research in the evaluation instrument withvalidity and reliability. The result of study accept broad scope characteristics,aggregation, integration, timeliness affect the performance of the organization. But,decentralization partially not moderate the relationship between broad scope,aggregation, integration, and timeliness but simultaneous decentralizationmoderating influence broad scope characteristics, aggregation, integration,timeliness to organizational performance.